2015
DOI: 10.1093/cid/civ092
|View full text |Cite
|
Sign up to set email alerts
|

Choice of Antiretroviral Drugs for Postexposure Prophylaxis for Adults and Adolescents: A Systematic Review

Abstract: The findings of this review provide evidence supporting the use of coformulated TDF and 3TC/FTC as preferred backbone drugs for PEP. Choice of third drug will depend on setting; for resource-limited settings, LPV/r is a reasonable choice, pending the improved availability of better-tolerated drugs with less potential for drug-drug interactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 36 publications
2
23
0
1
Order By: Relevance
“…In seven PEP studies published since 2001, 51% of the total 1009 participants reported at least one AE and about 20% failed to complete the 28-day course [5, 914]. The most common side effects we found were similar to those reported in studies with raltegravir, with similar frequency of nausea, vomiting, diarrhea, abdominal discomfort, headache, and fatigue but less myalgias or arthralgias [6, 7], which were reported only twice in our study.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…In seven PEP studies published since 2001, 51% of the total 1009 participants reported at least one AE and about 20% failed to complete the 28-day course [5, 914]. The most common side effects we found were similar to those reported in studies with raltegravir, with similar frequency of nausea, vomiting, diarrhea, abdominal discomfort, headache, and fatigue but less myalgias or arthralgias [6, 7], which were reported only twice in our study.…”
Section: Discussionsupporting
confidence: 70%
“…In well-resourced settings, a recent policy shift for HIV PEP has been toward combining TDF and FTC with raltegravir as the third drug even if data are still limited in this indication [6]. The short-term tolerability of a regimen including an integrase inhibitor as a third agent has been reported in some studies of raltegravir [4, 7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many of the PEP regimens used in these studies included poorly tolerated antiretroviral drugs. A recent systematic review reported that tenofovir disoproxil fumarate (TDF) based PEP was better tolerated with higher completion rates than zidovudine based PEP, which used to be the standard of care [14]. The WHO now recommends the use of TDF as part of the backbone for PEP regimens [15].…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral therapy was most often poorly tolerated; protocols should be optimised to maximise adherence 15. Studies also demonstrated that handing out the full 28 days of treatment at once rather than a 3-day starter pack improves compliance and facilitates the whole process for patients; this should be discussed according to the organisation in each reference centre 16.…”
Section: Discussionmentioning
confidence: 99%